2012
DOI: 10.1177/2047487312445000
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet, moderate-to-high intensity training, and health-related quality of life in adults with metabolic syndrome

Abstract: A model of hypocaloric Mediterranean diet combined with periodized moderate-to-high intensity training may lead to greater improvement in HRQoL through a greater effect on physical and functional fitness, bodyweight, and risk factors than diet alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 36 publications
(45 reference statements)
5
67
2
1
Order By: Relevance
“…Similarly, data from controlled randomized studies also confirm this association, revealing improvement in the MetS components, followed by better QOL scores after interventions to change lifestyle [28][29][30][31][32][33][34][35][36][37], in up to 24 months of follow-up [28]. Cohort studies assessing association between MetS and QOL corroborate these data, even though analyzing data in a different way.…”
Section: Introductionmentioning
confidence: 70%
“…Similarly, data from controlled randomized studies also confirm this association, revealing improvement in the MetS components, followed by better QOL scores after interventions to change lifestyle [28][29][30][31][32][33][34][35][36][37], in up to 24 months of follow-up [28]. Cohort studies assessing association between MetS and QOL corroborate these data, even though analyzing data in a different way.…”
Section: Introductionmentioning
confidence: 70%
“…6 Cardiorespiratory fitness is also associated with numerous cardiovascular risk factors reductions such as diabetes mellitus [DM], 7 hypertension, 8,9 and metabolic risk. 10,11 However, data on the association of objectively measured CRF and cardiovascular morbidity are limited, and only few studies have adequately controlled for confounding variables. 12 The aims of the current study were to (1) evaluate the association between CRF and the risk for developing acute coronary syndrome (ACS) in a large cohort of asymptomatic men and women and (2) investigate whether CRF has a direct or indirect effect through mediation by other cardiovascular risk factors on long-term risk for ACS in a large cohort of middle-aged adult males and females without known CHD.…”
mentioning
confidence: 99%
“…Various modalities of physical training -aerobic, aerobic interval, strength -are used in MetS subjects [10,23,24]. Since previous studies usually implemented 8 or more week duration training programmes in these subjects [9][10][11]25], we assessed if short 4-week duration supervised aerobic physical training could have some initial impact on anthropometric, metabolic, hemodynamic and arterial wall parameters in MetS subjects. We have demonstrated that short-duration supervised aerobic physical training improves anthropometric parameters, metabolic profile, and arterial wall parameters, and could serve as the initial step for continuous improvement of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of anthropometric, metabolic and arterial wall parameters occurring after supervised aerobic physical training could contribute to dynamic assessment of cardiovascular risk in MetS subjects and significantly enhance the motivation of these subjects for physically active lifestyle and physical training. Most of the previously conducted physical training interventional studies in MetS patients lasted 8 weeks and more [9][10][11]. Furthermore, none of them have compared the effects that occur as early as after 4 weeks of the supervised aerobic exercise training.…”
Section: Introductionmentioning
confidence: 99%